Notes and debate paper: Should merchandising and sourcing be worlds apart? The opportunity for more integrated strategic sourcing research. Issue 1 (January 2021) - van Hoek, Remko; Thomas, Rodney
Abstract: Whereas retailers are some of the biggest buyers that have some of the highest percentages of external spend as a share of revenue, they are not typically included in strategic sourcing research. Strategic sourcing research originated with a focus on supplies for manufacturing. But the strategic sourcing of merchandise by retailers is not as commonly studied. Merchandise sourcing is often approached very differently from manufacturing sourcing and often different teams of buyers with different roles and responsibilities are involved. Leveraging author industry experience and interviews with strategic sourcing executives in manufacturing and merchandise sourcing this notes and debate paper compares strategic sourcing across these domains and identifies fruitful research opportunities for developing a more comprehensive supply chain approach to strategic sourcing research. Highlights: Whereas retailers are some of the biggest buyers from suppliers and have some of the highest percentages of external spend as a share of revenue, they are not typically included in strategic sourcing research. Strategic sourcing research originated with a focus on supplies for manufacturing, with the strategic sourcing of services more recently added.Merchandise sourcing is often approached very differently from manufacturing and service sourcing and often different teams of buyers with different roles and responsibilities are involved. This paper compares strategic sourcing across these domains and identifies research opportunities for developing a more comprehensive supply chain approach to strategic sourcing research.